Natural-Geographical Features of Kizilkum - Mirsaid Jalilov; Umidjon Narzullaev; Jalilova Marjona (Genius Journals, 2021)
Scientists have proved that the Kyzylkum region has been occupied by humans since ancient times1. Kyzylkum is a country by its size. The Kyzylkum desert occupies a large part of the Turan plain and is located between the Syrdarya and Amudarya rivers.
Keywords: Kyzylkum; Ayakogitma; Neolithic; Uzbek-French joint archeological expedition